Hubungan Self Awareness Terhadap Penyesuaian Diri pada Siswa SMP di Kulon Progo - Tiara Candra Putri; Fildzah Malahati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to determine the relationship between self-awareness and self-adjustment in junior high school students in Kulon Progo Regency. This study used a correlational quantitative method with a sample of 104 students taken through cluster random sampling technique. The research instruments include a self-awareness scale that has been tested for validity and reliability, and a self-adjustment scale. The results of data analysis using Product Moment correlation technique showed a significant relationship between self-awareness and self-adjustment with a correlation coefficient of r=0.970r=0.970r=0.970 (p < 0.05). This finding indicates that self-awareness contributes significantly to students' ability to adjust, both in social and academic environments. The implication of this study shows the importance of developing self-awareness through training programs and reflective activities in schools to improve students' adjustment ability.